Ultrathin Visible‐Light‐Driven Mo Incorporating In2O3–ZnIn2Se4 Z‐Scheme Nanosheet Photocatalysts. Issue 5 (5th December 2018) - Chao, Yuguang; Zhou, Peng; Li, Na; Lai, Jianping; Yang, Yong; Zhang, Yelong; Tang, Yonghua; Yang, Wenxiu; Du, Yaping; Su, Dong; Tan, Yisheng; Guo, Shaojun
Abstract: Inspired by natural photosynthesis, the design of new Z‐scheme photocatalytic systems is very promising for boosting the photocatalytic performance of H2 production and CO2 reduction; however, until now, the direct synthesis of efficient Z‐scheme photocatalysts remains a grand challenge. Herein, it is demonstrated that an interesting Z‐scheme photocatalyst can be constructed by coupling In2 O3 and ZnIn2 Se4 semiconductors based on theoretical calculations. Experimentally, a class of ultrathin In2 O3 –ZnIn2 Se4 (denoted as In2 O3 –ZISe) spontaneous Z‐scheme nanosheet photocatalysts for greatly enhancing photocatalytic H2 production is made. Furthermore, Mo atoms are incorporated in the Z‐scheme In2 O3 –ZISe nanosheet photocatalyst by forming the MoSe bond, confirmed by X‐ray photoelectron spectroscopy, in which the formed MoSe2 works as cocatalyst of the Z‐scheme photocatalyst. As a consequence, such a unique structure of In2 O3 –ZISe–Mo makes it exhibit 21.7 and 232.6 times higher photocatalytic H2 evolution activity than those of In2 O3 –ZnIn2 Se4 and In2 O3 nanosheets, respectively. Moreover, In2 O3 –ZISe–Mo is also very stable for photocatalytic H2 production by showing almost no activity decay for 16 h test. Ultraviolet–visible diffuse reflectance spectra, photoluminescence spectroscopy, transient photocurrent spectra, and electrochemical impedance spectroscopy reveal that the enhanced photocatalytic performance of In2 O3 –ZISe–Mo is mainly attributed to its widened photoresponse range and effective carrier separation because of its special structure. Abstract : A new class of ultrathin In2 O3 –ZnIn2 Se4 (denoted as In2 O3 –ZISe) spontaneous Z‐scheme nanosheet photocatalysts is prepared for greatly enhancing photocatalytic H2 production. The incorporation of Mo atoms to the Z‐scheme In2 O3 –ZISe nanosheet photocatalyst by forming the MoSe bond can further boost the H2 evolution.